English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

solve for x

2007-02-04 04:48:50 · 13 answers · asked by chickiejam 1 in Science & Mathematics Mathematics

13 answers

6(x - 2) + 1 = 10x - 3 - 5x
6x - 12 + 1 = 10x - 3 - 5x
6x - 11 = 5x - 3 (Add 11 and subtract 5x from both sides)
x = 8

Check:
6(8 - 2) + 1 = 10(8) - 3 - 5(8)
6(6) + 1 = 80 - 3 - 40
36 + 1 = 37
37 = 37
QED

2007-02-04 04:55:42 · answer #1 · answered by CSUFGrad2006 5 · 1 0

Solve for "x" ... 6(x - 2) + 1 = 10x - 3 - 5x

First: eliminate parenthesis --- distribute the outer term with the terms in parenthesis...

6(x) + 6(- 2) + 1 = 10x - 3 - 5x

6x + (-12) + 1 = 10x - 3 - 5x

6x - 12 + 1 = 10x - 3 - 5x

*Combine "like" terms...

6x - 11 = 5x - 3

Sec: add 11 to both sides...

6x - 11 + 11 = 5x - 3 + 11

6x = 5x + 8

*Subtract 5x from both sides...

6x - 5x = 5x - 5x + 8

x = 8

2007-02-04 05:02:52 · answer #2 · answered by ♪♥Annie♥♪ 6 · 1 0

Eliminating parenthesis
6x - 12 + 1 = 10x - 3 - 5x

adding or grouping similar terms:
6x - 11 = 5x - 3

Adding 11 in both sides
6x - 11 + 11 = 5x - 3 + 11
6x = 5x + 8

substracting 5x in both sides:
6x - 5x = 5x - 5x + 8
x = 8

Proof:
6(8 - 2) + 1 = 10(8) - 3 - 5(8)
6(6) + 1 = 80 -3 - 40
36 + 1 = 80 - 43
37 = 37

2007-02-04 05:03:35 · answer #3 · answered by gquiroz2005 2 · 1 0

6(x-2) + 1 = 10x - 3 - 5x
6x - 12 + 1 = 10x - 5x - 3
6x - 10x + 5x = 12 - 1 - 3
x = 8

2007-02-04 04:54:55 · answer #4 · answered by Varun 1 · 1 0

6 (x-2) + 1 = 10x - 3 - 5x
6x - 12 + 1 = 10x - 3 - 5x
6x - 10x + 5x = -3 + 12 - 1
x = 8

2007-02-04 04:52:52 · answer #5 · answered by Anonymous · 1 0

6(x-2) +1 = 10x - 3 -5x

6x -12 + 1 = 5x -3

6x -11 = 5x -3

x = 8

2007-02-04 05:09:41 · answer #6 · answered by bignose68 4 · 1 0

6 (x-2) +1 = 10x - 3 - 5x

Distribute
6x - 12 +1 = 10x - 3 - 5x
Combine like terms
6x - 11 = 5x - 3
Bring x to left side (subtract 5x from each side)
x - 11 = - 3
Bring 11 to right side (add 11 to both sides)
x = 8

2007-02-04 04:56:01 · answer #7 · answered by ClooneyIsAGenius 2 · 1 0

6(x-2)+1 =10x-3-5x
6x - 12 +1 = 5x - 3
6x -11 = 5x - 3
x = 8

2007-02-04 04:52:49 · answer #8 · answered by Racin Girl 3 · 1 0

Multiply out the first term:
6x - 12 + 1 = 10x -3 - 5x
Now consolidate terms on each side of the equal sign:
6x -11 = 5x - 3
Subtract 5x from both sides:
x-11 = -3
Add 11 to both sides:
x = 8

2007-02-04 04:55:03 · answer #9 · answered by Jeff S 1 · 1 0

I havent finished this in a protracted time yet I gave it a shot. Subtract a million/2 on the main suitable ingredient from the three/4 on the main suitable ingredient. Now you have a million/4-2x/3=5x/6. Then subtract the 2x/3 from 5x/6. Now you have a million/4=5x/6. Then i think of of you circulate multiply to get 4x=6. Divide via utilising 4 to do away with it and you have x=6/4, which reduces into x=3/2.

2017-01-02 07:10:51 · answer #10 · answered by gerda 4 · 0 0

fedest.com, questions and answers